THE PERFORMANCE OF THE CZECH LABOUR MARKET AFTER THE 2004 EU ENLARGEMENT - Strielkowski, Wadim; Hněvkovský, Jan (Economic Annals, 2013)
This paper examines whether there has been a significant change in the performance of the Czech labour market after the Czech Republic’s EU Accession in May 2004. We analyse methodological changes of measuring unemployment caused by inevitable legislative adjustments and follow the development of the Czech labour market and the inflows of foreign workers to the Czech Republic over the past two decades. Our results show that the EU Accession resulted in simplifying foreigners’ access to the Czech labour market and did not cause a significant change in its performance. Our findings might be of some relevance for the countries seeking EU Membership in the near future (e.g., Serbia or Montenegro).